Low-Wavelengths SOI CMOS Photosensors for Biomedical Applications - Bulteel, Olivier; Overstraeten-Schlögel, Nancy Van; Afzalian, Aryan; Dupuis, Pascal; Jeumont, Sabine; Irenge, Leonid; Ambroise, Jérôme; Macq, Benoit; Gala, Jean-luc; Flandre, Denis (IntechOpen, 2011)
None